'Genius', 'Faction' and Rescuing Intellectual Property Rights - KINGSTON, WILLIAM (My University, 2005)
Intellectual property rights have been driven relentlessly towards a unitary system for the entire world, originally through passive copying of flawed United States arrangements, but more recently as a result of determined lobbying by American interests. But diversity and competition have the same beneficial potential for institutions themselves as they have for the economic development they can foster or hinder. A financial dimension in measuring grants, protecting innovation directly, compulsory technical arbitration of disputes, and some positive discrimination in favour of smaller firms could contribute to moving the balance back towards the diversity in rights that other countries need.
PUBLISHED
Keywords: Intellectual property rights; US Constitution; TRIPs